An assessment of the khat and vegetable trade in the local economic ecosystem: The case of northern Madagascar - Candicia M. Kotra; Lisa L. Gezon (PLoS ONE, 2026)
Background Khat is widely grown and consumed in parts of Africa. Its trade supports the local economy through income generation and tax contributions. This research explores the economic impact of khat production and trade in northern Madagascar by comparing its income with that of the vegetable trade. Methods We compared the profitability of khat and vegetable trading using a mixed-methods approach. Qualitative data were collected through interviews with nine city managers from two major khat-producing municipalities and with two key khat producers in the city of Diego-Suarez. Participant observation was also conducted at sales points across the city. Quantitative data were collected to twenty sellers to complement and validate the qualitative findings. Khat and vegetable sellers maintained daily income diaries to record variables such as income and purchase prices. Data were collected using KoboToolbox and entered via KoboCollect. In addition, to analyze longer-term financial trends, we examined five years of municipal financial statements from the two main production areas, Joffre-ville and Antsalaka.. Findings The results confirm our hypothesis that khat boosts local economic development by generating employment and municipal taxes that support infrastructure and local development. Further, khat selling proved to be more profitable than vegetable selling, with higher overall earnings despite seasonal price fluctuations. We found that vendors with family ties to khat farmers earn considerably more than others. Vegetables remain attractive to vendors who lack social contacts or capital to invest in khat, or who desire more market stability. Discussion and significance Overall, our findings confirm that khat plays a central and complementary role in the local economic ecosystem. Despite its controversial status as a psychoactive crop that is illegal in much of the world, we argue that it should be supported and regulated like other psychoactive crops such as tobacco, tea and coffee. Limitations Limitations include a small sample size, the complexity of the phenomenon, and data collection limited to a single year. Limitations were mitigated through in-depth qualitative research, and triangulation through informal interviews and field observations.